A method for rapid modification and preparation of ultra-thin aerogel composite materials
By soaking and rolling the substrate in a U-shaped container and combining rewinding and spraying modification technology, the problems of uneven thickness and long production cycle in the production of aerogel composites are solved, and the efficient preparation of ultra-thin aerogel composites is achieved, with excellent thermal insulation performance and production efficiency.
Patent Information
- Application Number
- CN202211720845.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The existing aerogel composite production methods are difficult to ensure the uniformity of product thickness and the shortening of production cycles, especially in the production of ultra-thin products, where there are problems of uneven substrate impregnation and bubbles, which affect the product appearance and production efficiency.
The substrate is impregnated with U-shaped containers, and the rewinding spray modification technology is used to ensure uniform thickness of the impregnated glue and shorten the production cycle. The specific steps include soaking the substrate in a U-shaped container and rolling it, rewinding and spraying modification after the gel gel ages, and finally obtaining ultra-thin aerogel composite material through supercritical drying.
The thickness uniformity and shortening of the production cycle of ultra-thin aerogel composite materials are achieved, the thermal conductivity of the room temperature is low, the hydrophobic rate is high, and the product tolerance range is within ±0.1mm, which improves production efficiency.
Smart Images

Figure CN116043540B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for rapidly modifying and preparing an ultra-thin aerogel composite material. Background Art
[0002] Aerogel is a new nano-material obtained by forming a nanostructure through condensation of colloidal particles or polymer molecules, and then replacing the liquid in the gel pores with gas through a special drying process while maintaining the gel skeleton structure without collapse. Aerogel composite materials are materials with excellent properties formed by the composite of aerogel and substrate materials. For example, the ultra-thin nano-aerogel insulation blanket made of inorganic fiber combined with silica aerogel has better tensile strength and hydrophobicity in addition to its low thermal conductivity, and is an ideal thermal insulation material for new energy vehicles and various industrial equipment.
[0003] At present, the main methods for mass production of aerogel composite products include crawler type and trough type, but both production methods have shortcomings. Among them, the crawler type production method cannot control the uniformity of product thickness, the substrate is not evenly impregnated, and there are spots on the surface of the product, especially for ultra-thin aerogel composite materials with a thickness of less than 1mm used in the new energy field. The tolerance of the product is more stringent, and the crawler type production method is difficult to meet. The trough type production method can effectively control the uniformity of product thickness, but it is prone to uneven substrate impregnation during the preparation of wet gels. At the same time, bubbles are prone to appear between the layers of aerogel composite materials produced by the trough type, affecting the appearance of the product. In addition, there is another problem with the existing aerogel composite production, that is, the production cycle is relatively long, generally 6 to 7 days, especially the modification process and supercritical drying process are the longest, which has always affected the production efficiency of aerogel products. Summary of the invention
[0004] In view of the above problems, the present invention provides a method for preparing ultra-thin aerogel composite materials by rapid modification, wherein the substrate is immersed in a U-shaped container and then rolled up to ensure uniform thickness of the dipped glue; and then the substrate is rewound and sprayed for modification to achieve rapid modification and shorten the production cycle of the aerogel material. The specific technical scheme is as follows:
[0005] A method for rapidly modifying and preparing an ultrathin aerogel composite material comprises the following steps:
[0006] 1) Prepare the dipping equipment: prepare a U-shaped trough as a dipping container, and a detachable winding shaft is provided in the U-shaped trough for winding the aerogel material after dipping;
[0007] 2) Preparation of gel solution: Mix ethyl orthosilicate, anhydrous ethanol, deionized water and catalyst in a certain proportion, stir evenly to form an aerogel solution for later use;
[0008] 3) Dipping the substrate: The coiled substrate is mounted on the unwinding roller, and one end of the substrate is fixed on the winding shaft provided in the U-shaped dipping tank after passing through the guide roller; the prepared aerogel solution is poured into the U-shaped dipping tank to ensure that the glue can soak the substrate; the unrolled substrate is soaked in the U-shaped dipping container and then rolled onto the winding disk; the speed and tension of the substrate unwinding and winding are adjusted to ensure the uniformity of the thickness of the prepared product; after the winding is completed, the glue is waited for the gel to age;
[0009] 4) Prepare for spraying: prepare the hydrophobic modifier according to the formula and add it to the spraying system to prepare for spraying modification of the aerogel;
[0010] 5) Rewinding spraying: After the gelling agent is aged, pour the wet gel roll out of the U-shaped container and place it on the wet gel winding device for rewinding; one end of the wet gel passes through the spraying system, passes through the guide roller and is fixed on another winding roller; adjust the spraying rate and spray the hydrophobic modifier evenly on the upper and lower surfaces of the wet gel material;
[0011] 6) Liquid phase hydrophobic modification: After the wet gel is rewound, it is placed in a modification tank to continue liquid phase hydrophobic modification;
[0012] 7) Supercritical drying: The modified ultra-thin wet gel roll is subjected to supercritical drying to obtain an ultra-thin aerogel composite material.
[0013] Preferably, in step 2), the mixing mass ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and catalyst is 1:1.5:0.2:0.002 to 1:9:0.2:0.006; the mixing process is: mixing tetraethyl orthosilicate and anhydrous ethanol, stirring for 10 minutes, adding deionized water after stirring evenly, and continuing to stir for 10 minutes. After the stirring is completed, adding the catalyst and stirring for 5 minutes to finally form an aerogel solution.
[0014] Preferably, in step 3), the aerogel solution is poured into a U-shaped dipping tank, and the position of the glue solution is higher than the position of the winding shaft to ensure that the glue solution can soak the substrate.
[0015] Preferably, in step 3), the substrate is one of wet-process glass fiber surface felt, basalt surface felt and ceramic fiber felt.
[0016] Preferably, the substrate thickness is ≤1 mm.
[0017] Preferably, in step 3), the unwinding tension of the substrate is 0-2A, the unwinding rate is 0-15m / min; the rotation speed of the winding shaft is 0-15m / min, and the winding tension is 0-4V.
[0018] Preferably, in step 4), the mass ratio of anhydrous ethanol to dimethyldiethoxysilane in the hydrophobic modifier is 1:0.1 to 1:1.
[0019] Preferably, in step 5), the rewinding spraying has a spraying rate of the hydrophobic modifier of 0 to 2 L / min.
[0020] Preferably, in step 6), the wet gel is modified in the modification tank for 5 to 15 hours.
[0021] Beneficial effects of the present invention:
[0022] 1) The ultra-thin aerogel product prepared by the method of the present invention has stable thermal insulation performance, and its thermal conductivity coefficient at room temperature is ≤0.014W / mK.
[0023] 2) The cycle of the product preparation method of the present invention is 4 days. Compared with the current traditional batch production method, the production cycle is greatly shortened and the production efficiency is improved.
[0024] 3) The aerogel material product prepared by the method of the present invention has excellent thickness uniformity. After testing, the tolerance range of the product is within ±0.1mm, which has good practical and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of substrate dipping in the rapid modification preparation method of the ultra-thin aerogel composite material of the present invention;
[0026] Figure 2 It is a schematic diagram of spray modification of the rapid modification preparation method of the ultra-thin aerogel composite material of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments and drawings to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only preferred embodiments of the present invention, not all embodiments, and are not intended to limit the present invention in other forms. Any technician familiar with the profession may use the disclosed technical content to make changes or modifications. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
[0028] Example 1
[0029] This embodiment is a method for rapidly modifying and preparing an ultrathin aerogel composite material, comprising the following steps:
[0030] 1) Prepare the dipping equipment: prepare a U-shaped trough as a dipping container, and a detachable winding shaft is provided in the U-shaped trough for winding the aerogel material after dipping;
[0031] 2) Preparation of gel solution: TEOS, anhydrous ethanol, deionized water and catalyst are mixed in a mass ratio of 1:5.8:0.2:0.004 to prepare an aerogel solution for later use; the mixing process is: TEOS and anhydrous ethanol are mixed, stirred for 10 minutes, deionized water is added after stirring evenly, and stirring is continued for 10 minutes. After the stirring is completed, the catalyst is added and stirred for 5 minutes to finally form an aerogel solution.
[0032] 3) Base material dipping: such as Figure 1 As shown, the substrate in the form of a coil is installed on the unwinding roller, and one end of the substrate is fixed on the winding shaft arranged in the U-shaped dipping tank after passing through the guide roller; the substrate is a kind of wet-process glass fiber surface felt, basalt surface felt, and ceramic fiber felt, and its thickness is ≤1mm. Pour the prepared aerogel solution into the U-shaped dipping tank, and the position of the glue liquid is higher than the position of the winding shaft to ensure that the glue liquid can soak the substrate; the unrolled substrate is soaked in the U-shaped dipping container and then wound onto the winding disk; adjust the rate and tension of substrate unwinding and winding to ensure the uniformity of the thickness of the prepared product, the unwinding tension of the substrate is 0~2A, and the unwinding rate is 0~15m / min; the rotation speed of the winding shaft is 0~15m / min, and the winding tension is 0~4V; after winding, wait for the glue liquid to gel and age;
[0033] 4) Prepare spraying: prepare a hydrophobic modifier according to the formula, wherein the mass ratio of anhydrous ethanol to dimethyldiethoxysilane in the hydrophobic modifier is 1:0.1 to 1:1, and add the hydrophobic modifier to the spraying system to prepare for spraying modification of the aerogel;
[0034] 5) Rewinding spray: After the glue gel is aged, pour the wet gel roll out of the U-shaped container and place it on the wet gel winding equipment for rewinding; Figure 2 As shown, one end of the wet gel passes through the spray system and is fixed on another winding roller after passing through the guide roller; the spray rate is adjusted, and the hydrophobic modifier is evenly sprayed on the upper and lower surfaces of the wet gel material; the spray rate of the hydrophobic modifier is 0 to 2 L / min.
[0035] 6) Liquid phase hydrophobic modification: After the wet gel is rewound, it is placed in a modification tank to continue liquid phase hydrophobic modification for 5 to 15 hours;
[0036] 7) Supercritical drying: The modified ultra-thin wet gel roll is subjected to supercritical drying to obtain an ultra-thin aerogel composite material.
[0037] Example 2
[0038] This embodiment is to prepare an ultra-thin aerogel composite material according to the preparation method in Example 1. The details are as follows:
[0039] Mix 38Kg of ethyl orthosilicate and 108Kg of anhydrous ethanol, stir for 10 minutes, add 9.3Kg of deionized water after stirring evenly, continue stirring for 10 minutes, add catalyst and stir for 5 minutes to finally form an aerogel solution. Pour the glue into the U-shaped container of the equipment for preparing wet gel products. Place the wet-process glass fiber surface felt coil with a roll diameter of 50cm and a thickness of 0.8mm in the unwinding position of the sol-gel equipment and fix it. Pull the substrate at the end to the winding shaft in the U-shaped container and fix it. At the same time, adjust the unwinding tension of the substrate and the winding tension of the winding shaft to 60Kg and 80Kg respectively, the unwinding rate and the winding rate are 10m / min, and after the winding shaft is wound, wait for the glue gel to age in the U-shaped groove. After aging, the whole roll of wet gel is transferred to the wet gel winding device for rewinding, and the end of the wet gel is pulled onto the winding disk. During the traction process, the wet gel passes through the atomization spray system. The wet gel unwinding rate and rewinding rate are 8m / min, and the tension is 90Kg. The wet gel winding device is turned on, and the atomization spray system is turned on at the same time. The mass ratio of anhydrous ethanol to dimethyldiethoxysilane in the hydrophobic modifier is 1:0.5, and the spray rate is 0.5L / min. After the wet gel is rewound, it is placed in the modification tank and left to stand for 14h. The modified wet gel product is subjected to CO2 supercritical drying to finally obtain an ultra-thin aerogel product. After testing, the thermal conductivity of the ultra-thin aerogel product at room temperature is 0.01357W / mK, and the hydrophobicity is 97.9%. The thickness test is carried out using a 30mm thickness gauge with a probe head. The results are shown in Table 1:
[0040] Table 1. Thickness test results of prepared ultra-thin aerogel composites
[0041]
[0042] Example 3
[0043] This embodiment also prepares the ultra-thin aerogel composite material according to the preparation method in Embodiment 1. The details are as follows:
[0044] Mix 50 kg of tetraethyl orthosilicate and 112 kg of anhydrous ethanol, stir for 10 minutes, add 9 kg of deionized water after stirring evenly, continue stirring for 10 minutes, add the catalyst and stir for 5 minutes to finally form an aerogel solution. Pour the glue into the U-shaped container of the equipment for preparing wet gel products. Place the basalt cotton surface felt coil with a roll diameter of 50 cm and a thickness of 0.6 mm in the unwinding position of the sol-gel equipment and fix it. Pull the substrate at the end to the winding shaft in the U-shaped container and fix it. At the same time, adjust the unwinding tension of the substrate and the winding tension of the winding shaft to 70 kg and 90 kg respectively, the unwinding rate and the winding rate to 12 m / min, and after the winding shaft is wound, wait for the glue to gel in the U-shaped groove for aging. After aging, the whole roll of wet gel is transferred to the wet gel winding device for rewinding, and the end of the wet gel is pulled onto the winding disk. During the pulling process, the wet gel passes through the atomization spray system. The wet gel unwinding rate and rewinding rate are 10m / min, and the tension is 90Kg. The wet gel winding device is turned on, and the atomization spray system is turned on at the same time. The mass ratio of anhydrous ethanol to dimethyldiethoxysilane in the hydrophobic modifier is 1:0.7, and the spray rate is 0.65L / min. After the wet gel is rewound, it is placed in the modification tank and left to stand for 16h. The modified wet gel product is subjected to CO2 supercritical drying to finally obtain an ultra-thin aerogel product. After testing, the thermal conductivity of the ultra-thin aerogel product at room temperature is 0.01289W / mK, and the hydrophobicity is 98.4%. The thickness gauge with a detection head of 30mm is used for testing. The results are shown in Table 2:
[0045] Table 2. Thickness test results of prepared ultra-thin aerogel composites
[0046]
[0047] Example 4
[0048] This embodiment also prepares the ultra-thin aerogel composite material according to the preparation method in Embodiment 1. The details are as follows:
[0049] Mix 70 kg of tetraethyl orthosilicate and 121 kg of anhydrous ethanol, stir for 10 minutes, add 13.6 kg of deionized water after stirring evenly, continue stirring for 10 minutes, add the catalyst and stir for 5 minutes to finally form an aerogel solution. Pour the glue into the U-shaped container of the equipment for preparing wet gel products. Place the ceramic fiber coil with a roll diameter of 50 cm and a thickness of 0.85 mm in the unwinding position of the sol-gel equipment and fix it. Pull the substrate at the end to the winding shaft in the U-shaped container and fix it. At the same time, adjust the unwinding tension of the substrate and the winding tension of the winding shaft to 60 kg and 80 kg respectively, the unwinding rate and the winding rate are 10 m / min, and after the winding shaft is wound, wait for the glue to gel in the U-shaped groove for aging. After aging, the whole roll of wet gel is transferred to the wet gel winding device for rewinding, and the end of the wet gel is pulled onto the winding disk. During the traction process, the wet gel passes through the atomization spray system. The wet gel unwinding rate and rewinding rate are 12m / min, and the tension is 90Kg. The wet gel winding device is turned on, and the atomization spray system is turned on at the same time. The mass ratio of anhydrous ethanol to dimethyldiethoxysilane in the hydrophobic modifier is 1:0.8, and the spray rate is 0.8L / min. After the wet gel is rewound, it is placed in the modification tank and left to stand for 18h. The modified wet gel product is subjected to CO2 supercritical drying to finally obtain an ultra-thin aerogel product. After testing, the thermal conductivity of the ultra-thin aerogel product at room temperature is 0.01257W / mK, and the hydrophobicity is 99.3%. The thickness gauge with a detection head of 30mm is used for testing. The results are shown in Table 3:
[0050] Table 3. Thickness test results of prepared ultra-thin aerogel composites
[0051]
[0052] In general, the present invention adopts the method of dipping and winding at the same time to produce sol-gel, which effectively solves the problem of uneven substrate dipping and the appearance of spots on the product surface, and strictly controls the thickness of the product. In the modification process, an atomization spray system is used to directly spray the modification liquid on the surface of the wet gel, which can shorten the hydrophobic modification time of the wet gel and effectively improve the production efficiency of the product. This method has broad application value in the production of ultra-thin aerogel products.
[0053] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0054] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in the embodiments may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for rapid modification and preparation of ultra-thin aerogel composite materials, characterized in that: The steps include: 1) Prepare the dipping equipment: prepare a U-shaped trough as a dipping container, and a detachable winding shaft is provided in the U-shaped trough for winding the aerogel material after dipping; 2) Preparation of gel solution: Mix ethyl orthosilicate, anhydrous ethanol, deionized water and catalyst in a certain proportion, stir evenly to form an aerogel solution for later use; 3) Dipping the substrate: Install the coiled substrate on the unwinding roller, and fix one end of the substrate on the winding shaft set in the U-shaped dipping tank after passing through the guide roller; pour the prepared aerogel solution into the U-shaped dipping tank to ensure that the glue can soak the substrate; the unrolled substrate is soaked in the U-shaped dipping container and then rolled onto the winding disk; adjust the speed and tension of substrate unwinding and winding to ensure the uniformity of the thickness of the prepared product; wait for the glue to gel after winding; pour the aerogel solution into the U-shaped dipping tank, and the position of the glue is higher than the position of the winding shaft to ensure that the glue can soak the substrate; When the unwinding rate and rewinding rate of the substrate are both 10m / min, the unwinding tension of the substrate is 60Kg, and the rewinding tension of the winding shaft is 80Kg; When the unwinding rate and rewinding rate of the substrate are both 12m / min, the unwinding tension of the substrate is 70Kg, and the rewinding tension of the winding shaft is 90Kg; 4) Prepare for spraying: prepare the hydrophobic modifier according to the formula and add it to the spraying system to prepare for spraying modification of the aerogel; 5) Rewinding spraying: After the gelling agent is aged, pour the wet gel roll out of the U-shaped container and place it on the wet gel winding device for rewinding; one end of the wet gel passes through the spraying system, passes through the guide roller and is fixed on another winding roller; adjust the spraying rate and spray the hydrophobic modifier evenly on the upper and lower surfaces of the wet gel material; 6) Liquid phase hydrophobic modification: After the wet gel is rewound, it is placed in a modification tank to continue liquid phase hydrophobic modification; 7) Supercritical drying: The modified ultra-thin wet gel roll is subjected to supercritical drying to obtain an ultra-thin aerogel composite material.
2. The method for rapidly modifying and preparing an ultrathin aerogel composite material according to claim 1, characterized in that: In step 2), the mixing mass ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and catalyst is 1:1.5:0.2:0.002-1:9:0.2:0.005; the mixing process is: mix tetraethyl orthosilicate and anhydrous ethanol, stir for 10 minutes, add deionized water after stirring evenly, continue stirring for 10 minutes, after the stirring is completed, add the catalyst and stir for 5 minutes to finally form an aerogel solution.
3. The method for rapid modification and preparation of ultra-thin aerogel composite materials according to claim 1, characterized in that: In step 3), the substrate is one of wet-process glass fiber surface felt, basalt surface felt and ceramic fiber felt.
4. The method for rapidly modifying and preparing an ultrathin aerogel composite material according to claim 3, characterized in that: The substrate thickness is ≤1 mm.
5. The method for rapid modification and preparation of ultra-thin aerogel composite materials according to claim 1, characterized in that: In step 4), the mass ratio of anhydrous ethanol to dimethyldiethoxysilane in the hydrophobic modifier is 1:0.1 to 1:
1.
6. The method for rapidly modifying and preparing an ultrathin aerogel composite material according to claim 1, characterized in that: In step 5), the rewinding spraying has a spraying rate of the hydrophobic modifier of 0.5 to 2 L / min.
7. The method for rapidly modifying and preparing an ultrathin aerogel composite material according to claim 1, characterized in that: In step 6), the wet gel is modified in the modification tank for 5 to 15 hours.
Citation Information
Patent Citations
Ultrathin aerogel composite material and method for preparing same
CN107129262A
Preparation method of gel felt, equipment for preparing gel felt and aerogel felt
CN114477949A
Equipment and method for simultaneously producing gel felt body and modified gel body
CN115073127A